Monascus purpureus-fermented common buckwheat protects against dyslipidemia and non-alcoholic fatty liver disease through the regulation of liver metabolome and intestinal microbiome. (October 2020) - Huang, Zi-Rui; Chen, Min; Guo, Wei-Ling; Li, Tian-Tian; Liu, Bin; Bai, Wei-Dong; Ai, Lian-Zhong; Rao, Ping-Fan; Ni, Li; Lv, Xu-Cong
Graphical abstract: Highlights: M. purpureus- fermented common buckwheat has the potential to prevent NAFLD and dyslipidemia. M. purpureus- fermented common buckwheat consumption significantly changed the hepatic metabolic profiles. M. purpureus- fermented common buckwheat consumption modulated the intestinal microbial populations. Hepatic mRNAs involved in lipid metabolism were regulated by M. purpureus- fermented common buckwheat. Abstract: Monascus -fermented rice has been used to treat digestive disorder and promote blood circulation in China and other Asian countries for centuries. However, the effects and mechanisms of Monascus purpureus -fermented common buckwheat (HQ) on non-alcoholic fatty liver disease (NAFLD) and dyslipidemia are unclear. Here, oral supplementation of HQ significantly inhibited the abnormal growth of body weight and epididymal white adipose tissue (eWAT), prevented the hypertrophy of epididymal adipocytes, ameliorated some biochemical parameters of serum and liver related to lipid metabolism in mice fed a high-fat and high-cholesterol diet (HFD). Histological analysis also showed that the excessive accumulation of lipid droplets in the livers induced by HFD-feeding was greatly alleviated by HQ supplementation. Metagenomic analysis revealed that HQ supplementation made significant structural changes in the intestinal microflora of mice fed with HFD. The Spearman's correlation analysis revealed that physiological index, serum and liver lipid profiles were positively correlated with Bacteroidales S24-7, Streptococcus, Allobaculum, and Clostridiales XIII, but negatively associated with Lactobacillus, Ruminococcaceae_ NK4A214 group, Ruminiclostridium, and Alistipes . UPLC-QTOF/MS-based liver metabolomics demonstrated that HQ intervention had significant regulatory effects on the metabolic pathways of primary bile acid biosynthesis, pyrimidine metabolism, ether lipid metabolism, glutathione metabolism, glycine, serine and threonine metabolism, and amino sugar and nucleotide sugar metabolism, etc. Additionally, HQ intervention regulated the mRNA levels of hepatic genes involved in hepatic lipid metabolism and bile acid homeostasis. Collectively, these findings present new evidence supporting that HQ has the potential to ameliorate dyslipidemia and NAFLD via modulating the intestinal microbial populations and hepatic metabolite profile in hyperlipidemic mice induced by HFD.